ROLE OF COUNSELORS IN MOTIVATING ATHLETES GULAT WEST SUMATRA ON PON XIX - Sin, Tjung Hauw (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Motivation is one of the most important aspects of sports coaching program. Various facilities for athletes overcoming psychological problems should be held, including counseling program conducted by professional counselors. Athletes sports wrestling West Sumatra PON XIX get motivation increases with counseling by a counselor and motivator of the team during the preparation and training, so we get the result of increased achievement and medal counts for PON XIX. The results showed that counseling provides a constructive role to increase the motivation of athletes wrestling West Sumatra PON XIX.